Aplikasi Plant Growth Promoting Rhizobacteria (PGPR) untuk Mewujudkan Pertanian yang Sehat di Desa Kutamaneuh, Karawang - Maudy Susanti; Dede Kismantoro; Titiek S. Yuliani; Megayani Sri Rahayu; Iskandar Lubis; Fitriyah Nurul (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Kutamaneuh Village is a village that has abundant natural resources especially in the agriculture sector. One of the potentials of Kutamaneuh Village in the agricultural sector is the production of rice and horticultural crops which are one of the sources of family food providers and require healthy plant cultivation. Problems experienced by farmers in Kutamaneuh Village are pests and diseases encountered in plants. The socialization program and practice demo of making PGPR needs to be carried out with the aim of implementing the PGPR application, introducing healthy plant cultivation techniques and applying GAP principles to realize healthy agriculture and avoiding pests and plant diseases. This activity is carried out with a participatory method that applies the approach method in which the people of Kutamaneuh Village are the subjects in every activity, starting from planning, implementation, and evaluation. This activity was carried out in each hamlet with a series of activities in the form of socialization and demonstration of the practice of making PGPR. An indicator of the success of this program is that farmers implement good crop cultivation, plants taht are given PGPR treatment grow better than plants without PGPR treatment. This is also supported by a questionnaire indicator which shows that the socialization program and practical demonstration regarding PGPR in Kutamaneuh Village were successfully implemented. The socialization activities and demonstration of the practice of making PGPR were greeted with positive enthusiasm by the training participants. The application of PGPR in the village of Kutamaneuh to create a healthy crop and avoid the attack of intruding organisms so as to reduce the use of chemical fertilizers that have a negative impact on agricultural land. Keywords: Kutamaneuh Village, Pests, Disease, Healthy Agriculture, PGPR